Export duration and export product quality of firms: evidence from China - Wen Yue (Journal of Applied Economics, 2023)
ABSTRACTThis study analyzes how export duration affects firms’ export product quality. On the basis of Chinese firms’ micro data, we find that export duration has a significantly positive effect on the export product quality of firms by promoting their productivity and innovation ability. This study shows that the effect of export duration on the product quality of firms is not only reflected in the stage when they enter the export market. After entering the export market, the extension of export duration is also conducive to the improvement of firms’ product quality, supporting the wide presence of the effects of learning by exporting. Therefore, this study provides new empirical evidence to further understand the influence of export market on firms’ product quality.